2016
DOI: 10.18632/oncotarget.11688
|View full text |Cite
|
Sign up to set email alerts
|

Direct interaction of Ikaros and Foxp1 modulates expression of the G protein-coupled receptor G2A in B-lymphocytes and acute lymphoblastic leukemia

Abstract: Ikaros and Foxp1 are transcription factors that play key roles in normal lymphopoiesis and lymphoid malignancies. We describe a novel physical and functional interaction between the proteins, which requires the central zinc finger domain of Ikaros. The Ikaros-Foxp1 interaction is abolished by deletion of this region, which corresponds to the IK6 isoform that is commonly associated with high-risk acute lymphoblastic leukemia (ALL). We also identify the Gpr132 gene, which encodes the orphan G protein-coupled rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 48 publications
(52 reference statements)
0
10
0
Order By: Relevance
“…2a) including canonical plasma and memory cell differentiation genes such as Irf4 and Prdm1, as well as Cd80, which is important for B cell induction of follicular helper T (T FH ) cells 17 , Cxcr3, which plays a critical role in plasma cell differentiation 18 and Stat4, which induces plasma cell differentiation in GC B cells downstream of IL-12 19 . Lsd1 loss of function also yielded upregulation of Gpr132 , a gene that suppresses the proliferation of B cells 20 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2a) including canonical plasma and memory cell differentiation genes such as Irf4 and Prdm1, as well as Cd80, which is important for B cell induction of follicular helper T (T FH ) cells 17 , Cxcr3, which plays a critical role in plasma cell differentiation 18 and Stat4, which induces plasma cell differentiation in GC B cells downstream of IL-12 19 . Lsd1 loss of function also yielded upregulation of Gpr132 , a gene that suppresses the proliferation of B cells 20 .…”
Section: Resultsmentioning
confidence: 99%
“…Failure to proliferate could also be linked to upregulation of genes that inhibit cell cycle progression. One of these genes, the orphan G-coupled receptor Gpr132 was shown to arrest cell cycle progression in B cells downstream of IKZF 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Knockout mouse models have established a putative tumor suppressive role of GPR132 in leukemia and analysis of primary leukemic samples has revealed high GPR132 expression [123] , [126] . High GPR132 expression is inconsistent with a tumor suppressor role and may not necessarily be associated with functional activation.…”
Section: Imipridone Chemical Scaffold and Onc201 Analogsmentioning
confidence: 99%
“…Initially characterized by germline deletion, in this study, we identified FOXP1 loss in the mouse as a requirement for pro-B to pre-B cell transition. In humans, this transition is often breached in acute lymphocytic leukemia, and FOXP1 loss or gain has been the culprit in several cases (19,(96)(97)(98). FOXP1 has been recognized as an oncogene in various mature B cell tumors, such as non-Hodgkin lymphomas (24,99).…”
Section: Convergent Analyses Of Foxp1 B Cell Biologymentioning
confidence: 99%